Engineered Radiative Cooling Systems for Thermal-Regulating and Energy-Saving Applications - Lei, Leqi; Wu, Ting; Shi, Shuo; Si, Yifan; Zhi, Chuanwei; Huang, Kaisong; Yang, Jieqiong; Liang, Xinshuo; Zhu, Shanshan; Qu, Jinping; Hu, Jinlian (Nano-Micro Letters, 2025)
Radiative cooling systems (RCSs) possess the distinctive capability to dissipate heat energy via solar and thermal radiation, making them suitable for thermal regulation and energy conservation applications, essential for mitigating the energy crisis. A comprehensive review connecting the advancements in engineered radiative cooling systems (ERCSs), encompassing material and structural design as well as thermal and energy-related applications, is currently absent. Herein, this review begins with a concise summary of the essential concepts of ERCSs, followed by an introduction to engineered materials and structures, containing nature-inspired designs, chromatic materials, meta-structural configurations, and multilayered constructions. It subsequently encapsulates the primary applications, including thermal-regulating textiles and energy-saving devices. Next, it highlights the challenges of ERCSs, including maximized thermoregulatory effects, environmental adaptability, scalability and sustainability, and interdisciplinary integration. It seeks to offer direction for forthcoming fundamental research and industrial advancement of radiative cooling systems in real-world applications. Highlights: 1 This review thoroughly encapsulates the contemporary advancements in radiative cooling systems, from materials to applications. 2 Comprehensive discussion of the fundamental concepts of radiative cooling systems, engineered materials, thermal-regulating textiles and energy-saving devices. 3 The review critically evaluates the obstacles confronting radiative cooling systems, offering insightful and forward-looking solutions to shape the future trajectory of the discipline.